Change and Continuity Revisited: The View from Kesteven (Lincolnshire) - Gardiner, Mark; Hamilton-Bing, Annabelle (Medieval Settlement Research, 2024)
The LiDAR data from villages and other settlements in southern Lincolnshire are analysed and interpreted. The results are compared with previously published work from the north-west of the county. The new study showed that medieval settlement in the south of Kesteven was strongly nucleated with no evidence of farmsteads beyond the villages and hamlets. The only exception were the monastic granges and moated sites which were established in new locations. Most villages show some signs of contraction in the post-medieval period, and often of subsequent reoccupation. Consequently, the modern or even late nineteenth-century form of settlements may be a very poor guide to their medieval plan. Amongst the sites newly recognised are the meeting site of a thing or assembly, and the boundary enclosure of a minster church.